How Robust Are Social Structural Predictors of Carbon Dioxide Emissions? A Multiverse Analysis. Issue 1 (2nd January 2023) - Theis, Nicholas; York, Richard
ABSTRACT: Due to the many plausible decisions researchers can make during the scientific process, varying results can be obtained to research questions. In the environmental sociological literature, key theories and findings highlight how modernization, militarization, demographic factors, and globalization and trade influence carbon dioxide emissions. We use multiverse analysis to address how robust central findings in this literature are to model specification choices. Our results indicate that findings related to modernization and demographic factors are mostly robust, while those concerning militarization and globalization are more subject to model selection.